Congenital second branchial cleft anomalies in children: A report of 52 surgical cases, with emphasis on characteristic CT findings - Chen, Wei; Zhou, Yilong; Xu, Mengrou; Xu, Rong; Wang, Qingyu; Xu, Hongming; Chen, Jiarui; Li, Xiaoyan (Frontiers in Pediatrics, 2023)
Objective: To review the clinical features and surgical treatment outcomes of congenital second branchial cleft anomalies (CSBCAs), and to investigate the characteristic CT findings of CSBCAs. Methods: We conducted a retrospective study of 52 children who were referred to Shanghai Children’s Hospital from October 2014 to December 2021 diagnosed as CSBCAs. Results: There were 36 males and 16 females. Of them, 35 patients were presented as having a skin pit at birth or discharge from the skin opening on the lateral neck, and 17 patients showed an asymptomatic or painful mass. The typical CT features of CSBCAs included isolated and homogeneously hypodense cystic lesions surrounded by a uniformly thin, smooth wall. CSBCAs were generally located at the anteromedial border of the sternocleidomastoid muscle, posterior to the submandibular gland, and lateral to the carotid sheath. All patients were treated surgically and only 1 case underwent ipsilateral tonsillectomy. After a median follow up of 30 (range 4 90) months, no recurrence or complications were observed. Conclusions: The CSBCAs show some characteristic CT findings, which can help clinicians diagnose and plan surgical strategies. High ligation of the lesions is sufficient for complete excision of CSBCAs.